Optimal. Leaf size=30 \[ \frac {\left (-e^2+x\right ) \left (4 e^{\frac {1}{(-2-x) x}}+3 x\right )}{x} \]
________________________________________________________________________________________
Rubi [F] time = 1.08, antiderivative size = 0, normalized size of antiderivative = 0.00, number of steps used = 0, number of rules used = 0, integrand size = 0, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.000, Rules used = {} \begin {gather*} \int \frac {12 x^3+12 x^4+3 x^5+e^{-\frac {1}{2 x+x^2}} \left (8 x+8 x^2+e^2 \left (-8+8 x+16 x^2+4 x^3\right )\right )}{4 x^3+4 x^4+x^5} \, dx \end {gather*}
Verification is not applicable to the result.
[In]
[Out]
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\int \frac {12 x^3+12 x^4+3 x^5+e^{-\frac {1}{2 x+x^2}} \left (8 x+8 x^2+e^2 \left (-8+8 x+16 x^2+4 x^3\right )\right )}{x^3 \left (4+4 x+x^2\right )} \, dx\\ &=\int \frac {12 x^3+12 x^4+3 x^5+e^{-\frac {1}{2 x+x^2}} \left (8 x+8 x^2+e^2 \left (-8+8 x+16 x^2+4 x^3\right )\right )}{x^3 (2+x)^2} \, dx\\ &=\int \left (3+\frac {4 e^{-\frac {1}{x (2+x)}} \left (-2 e^2+2 \left (1+e^2\right ) x+2 \left (1+2 e^2\right ) x^2+e^2 x^3\right )}{x^3 (2+x)^2}\right ) \, dx\\ &=3 x+4 \int \frac {e^{-\frac {1}{x (2+x)}} \left (-2 e^2+2 \left (1+e^2\right ) x+2 \left (1+2 e^2\right ) x^2+e^2 x^3\right )}{x^3 (2+x)^2} \, dx\\ &=3 x+4 \int \left (-\frac {e^{2-\frac {1}{x (2+x)}}}{2 x^3}+\frac {e^{-\frac {1}{x (2+x)}} \left (1+2 e^2\right )}{2 x^2}+\frac {e^{2-\frac {1}{x (2+x)}}}{8 x}+\frac {e^{-\frac {1}{x (2+x)}} \left (-2-e^2\right )}{4 (2+x)^2}-\frac {e^{2-\frac {1}{x (2+x)}}}{8 (2+x)}\right ) \, dx\\ &=3 x+\frac {1}{2} \int \frac {e^{2-\frac {1}{x (2+x)}}}{x} \, dx-\frac {1}{2} \int \frac {e^{2-\frac {1}{x (2+x)}}}{2+x} \, dx-2 \int \frac {e^{2-\frac {1}{x (2+x)}}}{x^3} \, dx+\left (-2-e^2\right ) \int \frac {e^{-\frac {1}{x (2+x)}}}{(2+x)^2} \, dx+\left (2 \left (1+2 e^2\right )\right ) \int \frac {e^{-\frac {1}{x (2+x)}}}{x^2} \, dx\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.53, size = 29, normalized size = 0.97 \begin {gather*} 3 x+\frac {4 e^{-\frac {1}{2 x+x^2}} \left (-e^2+x\right )}{x} \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [A] time = 0.61, size = 30, normalized size = 1.00 \begin {gather*} \frac {3 \, x^{2} + 4 \, {\left (x - e^{2}\right )} e^{\left (-\frac {1}{x^{2} + 2 \, x}\right )}}{x} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [A] time = 0.23, size = 48, normalized size = 1.60 \begin {gather*} \frac {3 \, x^{2} - 4 \, e^{\left (\frac {2 \, x^{2} + 4 \, x - 1}{x^{2} + 2 \, x}\right )}}{x} + 4 \, e^{\left (-\frac {1}{x^{2} + 2 \, x}\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.22, size = 27, normalized size = 0.90
method | result | size |
risch | \(3 x -\frac {4 \left ({\mathrm e}^{2}-x \right ) {\mathrm e}^{-\frac {1}{x \left (2+x \right )}}}{x}\) | \(27\) |
norman | \(\frac {-12 x^{2}+\left (8-4 \,{\mathrm e}^{2}\right ) x^{2} {\mathrm e}^{-\frac {1}{x^{2}+2 x}}+3 x^{4}+4 x^{3} {\mathrm e}^{-\frac {1}{x^{2}+2 x}}-8 x \,{\mathrm e}^{2} {\mathrm e}^{-\frac {1}{x^{2}+2 x}}}{x^{2} \left (2+x \right )}\) | \(81\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [A] time = 0.46, size = 29, normalized size = 0.97 \begin {gather*} 3 \, x + \frac {4 \, {\left (x - e^{2}\right )} e^{\left (\frac {1}{2 \, {\left (x + 2\right )}} - \frac {1}{2 \, x}\right )}}{x} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 4.72, size = 37, normalized size = 1.23 \begin {gather*} 3\,x+4\,{\mathrm {e}}^{-\frac {1}{x^2+2\,x}}-\frac {4\,{\mathrm {e}}^{-\frac {1}{x^2+2\,x}}\,{\mathrm {e}}^2}{x} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [A] time = 0.22, size = 22, normalized size = 0.73 \begin {gather*} 3 x + \frac {\left (4 x - 4 e^{2}\right ) e^{- \frac {1}{x^{2} + 2 x}}}{x} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________